2021
DOI: 10.1038/s41396-021-01044-3
|View full text |Cite
|
Sign up to set email alerts
|

Methane-dependent selenate reduction by a bacterial consortium

Abstract: Methanotrophic microorganisms play a critical role in controlling the flux of methane from natural sediments into the atmosphere. Methanotrophs have been shown to couple the oxidation of methane to the reduction of diverse electron acceptors (e.g., oxygen, sulfate, nitrate, and metal oxides), either independently or in consortia with other microbial partners. Although several studies have reported the phenomenon of methane oxidation linked to selenate reduction, neither the microorganisms involved nor the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 83 publications
3
13
0
Order By: Relevance
“…During the whole denitrification process involving a series of enzymes, nitrate and nitrite reductases are responsible for producing and consuming nitrite. Consistent with the observation of nitrate reduction, the microbial consortium harbored 11 periplasmic nitrate reductase genes ( napA ) and 16 respiratory nitrate reductase genes ( narG ), both belonging to the dimethyl sulfoxide reductase (DMSOR) family (Figure a) . The gene and transcript abundances of napA were obviously decreased, as well as the absolute transcription level, after acetate was replaced with H 2 as the sole electron donor (Figure b,c).…”
Section: Resultssupporting
confidence: 73%
“…During the whole denitrification process involving a series of enzymes, nitrate and nitrite reductases are responsible for producing and consuming nitrite. Consistent with the observation of nitrate reduction, the microbial consortium harbored 11 periplasmic nitrate reductase genes ( napA ) and 16 respiratory nitrate reductase genes ( narG ), both belonging to the dimethyl sulfoxide reductase (DMSOR) family (Figure a) . The gene and transcript abundances of napA were obviously decreased, as well as the absolute transcription level, after acetate was replaced with H 2 as the sole electron donor (Figure b,c).…”
Section: Resultssupporting
confidence: 73%
“…Overall, reaction stoichiometry, metagenomic analyses, and metabolite measurements all support a synergistic nature of methane-dependent arsenate reduction, carried out by the aerobic methanotrophs and members of Burkholderiaceae, with formate as the interspecies electron carrier. Formate is well known to support methanogenesis-based syntrophy and was demonstrated to mediate the methane-oxidation-based selenate reduction recently . The present study provides another clear example for formate coupling aeMO to the reduction of oxides, highlighting the possibility that similar trophic relationships may link methane metabolism to a range of terminal electron acceptors in (hyp)­oxic environments.…”
Section: Resultsmentioning
confidence: 56%
“…Formate is well known to support methanogenesis-based syntrophy 74−76 and was demonstrated to mediate the methane-oxidation-based selenate reduction recently. 77 The present study provides another clear example for formate coupling aeMO to the reduction of oxides, highlighting the possibility that similar trophic relationships may link methane metabolism to a range of terminal electron acceptors in (hyp)oxic environments.…”
Section: Aerobic Methane Oxidation Coupled To Arsenatementioning
confidence: 99%
“…For instance, methanotrophs are widely distributed in freshwater sediment and groundwater and have been reported to metabolize methane under oxygen-limited conditions and produce formate. The methane-derived products can be further utilized by synergistic populations. , Environmental surveys also suggested that methanotrophs thrive under hypoxic conditions where ANME are active. , This implies a potential syntrophic relationship between methanotrophs and ANME in environments with limited methane and/or oxygen.…”
Section: Resultsmentioning
confidence: 99%